Consultant-led triage of paediatric hospital referrals: a service evaluation. Issue 1 (22nd February 2021) - Hodgson, Heather Sharon; Webb, Nicholas; Diskin, Lynn
Abstract : Objective: We established a paediatric demand management (PDM) service in our paediatric department in 2017. The aim of this consultant-delivered service is to manage referrals more efficiently by providing active triage of all referrals, daily rapid access clinics and easily accessible advice for primary healthcare professionals. This study presents an evaluation of this service. Design: Mixed-methods service evaluation with analysis of data for every contact with the PDM service over a 2-year period. For each patient, the method of contact, reason for contact, presenting complaint and triage outcome were recorded. Feedback from general practitioners (GPs) and patients was gathered. Results: Data were analysed for 7162 patients. More than a quarter (2034; 28%) of all referrals were managed with advice only. Of the 4703 outpatient clinic referrals, 1285 (27%) were managed without a clinic appointment. More than half (54%) of the requests for paediatric assessment unit (PAU) admission were managed alternatively, typically with advice only or a rapid access clinic appointment. This has reversed the increasing trend of PAU admissions from primary care of preceding years. Financial analysis suggested the avoidance of these clinic appointments, and PAU admissions provided a substantial cost saving. Conclusions: Our results indicate that the PDM service has succeeded in reducing unnecessary hospital attendances by managing patients more effectively and strengthening partnerships with primary care. The service has received overwhelmingly positive feedback from GPs. This service could be replicated in other Trusts and developed in the future to facilitate further management of paediatric cases in a primary care setting.